A novel microRNA regulates cooperation between symbiont and a laterally acquired gene in the regulation of pantothenate biosynthesis within Bemisia tabaci whiteflies. Issue 9 (14th March 2022) - Sun, Xiang; Liu, Bing‐Qi; Li, Chu‐Qiao; Chen, Zhan‐Bo; Xu, Xiao‐Rui; Luan, Jun‐Bo
Abstract: Horizontally transferred genes (HTGs) play a key role in animal symbiosis, and some horizontally transferred genes or proteins are highly expressed in specialized host cells (bacteriocytes). However, it is not clear how HTGs are regulated, but microRNAs (miRNAs) are prime candidates given their previously demonstrated roles in symbiosis and impacts on the expression of host genes. A horizontally acquired PanBC that is highly expressed in whitefly bacteriocytes can cooperate with an obligate symbiont Portiera for pantothenate production, facilitating whitefly performance and Portiera titre. Here, we found that a whitefly miRNA, novel‐m0780‐5p, was up‐regulated and its target panBC was down‐regulated in Portiera ‐eliminated whiteflies. This miRNA was located in the cytoplasmic region of whitefly bacteriocytes. Injection of novel‐m0780‐5p agomir reduced the expression of PanBC in whitefly bacteriocytes, while injection of novel‐m0780‐5p antagomir enhanced PanBC expression. Agomir injection also reduced the pantothenate level, Portiera titre and whitefly performance. Supplementation with pantothenate restored Portiera titre and the fitness of agomir‐injected whiteflies. Thus, we demonstrate that a whitefly miRNA regulates panBC ‐mediated host–symbiont collaboration required for pantothenate synthesis, benefiting the whitefly– Portiera symbiosis. Both panBC and novel‐m0780‐5p are present in the genomes of six Bemisia tabaci species. The expression of a novel miRNA in multiple B . tabaci species suggests that the miRNA evolved after panBC acquisition, and allowed this gene to be more tightly regulated. Our discovery provides the first account of a HTG being regulated by a miRNA from the host genome, and suggests key roles for interactions between miRNAs and HTGs in the functioning of symbiosis.